A work study on Miledel Enterprises (makers of the QB Stainless Grill) - Duque, Ricci (College of Engineering, 1998)
Miledel Enterprises is a single proprietorship that manufactures and sells charcoal stoves and grills to the public. The enterprise has six functions and these are : product development, purchasing, industrial relations, manufacturing, marketing and internal finance. The company produces three kinds of products. The group chose to study the manufacturing department of the business and determine the present problems in the manufacture of the QB Stainless Charcoal Grill. The present problems of the manufacturing department are: 1) Poor work practices and lack of manufacturing procedures. 2) Long lead time for the manufacture of a single grill unit. 3) Absence of an efficient plant layout/comfortable workplace layout. The recommendations of the group are : 1) The transition of the manufacturing department into an efficient assembly line. 2) The improvement of existing plant layout by rearranging the whole factory into a functional type layout including the rearrangement of the storage areas. 3) The improvement of workplace layout by standardizing the chairs and tables of each workstation. 4) The introduction of a new role or position which is the plant supervisor to help monitor the manufacturing department. The most probable result of these recommendations is the improvement of the present 4.25 hrs/grill rate to a projected 3.753 hrs/grill rate of production.